2020
DOI: 10.3390/pr8050505
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Large-Scale Bio-Hydrogen Network Using Waste Gas from Landfill and Anaerobic Digestion: A P-Graph Approach

Abstract: Due to the expanding concern on cleaner production and sustainable development aspects, a technology shift is needed for the hydrogen production, which is commonly derived from natural gas. This work aims to synthesise a large-scale bio-hydrogen network in which its feedstock, i.e., bio-methane, is originated from landfill gas and palm oil mill effluent (POME). Landfill gas goes through a biogas upgrader where high-purity bio-methane is produced, while POME is converted to bio-methane using anaerobic digestor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…According to the study of [73], eco-design is a renovation approach towards product which considers the environmental impacts of its entire life cycle. Eco-design not only lowers environmental impact but also focuses on resource effectiveness [74]. Other major elements that need to be considered while developing or innovating the eco-product are reducing material intensity, renewable energy intensity, product climate change, product recyclability, and durability.…”
Section: Discussionmentioning
confidence: 99%
“…According to the study of [73], eco-design is a renovation approach towards product which considers the environmental impacts of its entire life cycle. Eco-design not only lowers environmental impact but also focuses on resource effectiveness [74]. Other major elements that need to be considered while developing or innovating the eco-product are reducing material intensity, renewable energy intensity, product climate change, product recyclability, and durability.…”
Section: Discussionmentioning
confidence: 99%
“…Conversion ratios of processes, amount of hydrogen production, hydrogen demand, facilities location and other references are the basic information needed to model the network structure. The methodology for P-graph construction is adopted from the studies of Hemmati et al [9]. Subsequently, the top three ranked optimal bio-hydrogen were simulated via Monte Carlo simulation model to evaluate the financial profitability of the aforementioned supply chain.…”
Section: Methodsmentioning
confidence: 99%
“…Process eco-innovation demonstrated that a cleaner production process can be incorporated into the industrial manufacturing process without negotiating sustainability, societal development, and most importantly the circular economy [39][40][41][42]. Cleaner production is an approach that accumulates various production factors such as shortening the greenhouse emission force, water concentration, waste concentration, energy application, and reprocessing or recycling the materials [38][39][40][41]43]. The other significant division can be rainwater application and growing renewable energy.…”
Section: Model-2 Proactive Process Eco-innovation and Firm Financial Performancementioning
confidence: 99%